Identifying Desirable Competencies for Supply Chain Management Professionals - David Marshall; Wei-Cheng Milton Shen (ExcelingTech, 2023)
As the human dimension becomes increasingly critical to overall success of supply chain management (SCM), practitioners, researchers, and educators face the daunting task of identifying requisite competencies for SCM professionals. By using a large, frequently-updated, publicly-available archive – O*NET, this research contrasts SCM and other business professionals to highlight the unique competencies that define the SCM profession. We find that SCM professionals need greater functional knowledge about operations (e.g., transportation, production), higher general knowledge in geography and foreign language, extensive interpersonal skills, and a person-oriented management style. Furthermore, while limited differences exist between purchasing and logistic managers in the SCM profession, they exhibit certain competencies that distinguish them from operation managers. Such results inform efforts at curriculum design, recruitment, career development, and corporate training by suggesting areas where it may well be advantageous to customize efforts toward ensuring that requisite competencies are addressed.